The reproduction of educational inequalities – do parenting and child behavioural problems matter? - Till Kaiser; Jianghong Li; Matthias Pollmann-Schult (Acta Sociologica, 2019)
The strong link between parental socioeconomic status (SES) and children's success in school is well established. However, mechanisms that underpin this association remain a major issue in current research on social inequality. Using data from the Families in Germany Study and structural equation modelling, this study demonstrates that parenting styles and child behavioural problems explain, in part, the association between parental SES and child school grades for mathematics and German between the ages of 9 and 10. We found that parents with a low SES are more likely to be inconsistent in their parenting and to use psychological control with their children more often, these two factors being linked to child behavioural problems. Adverse parenting and behavioural problems are, in turn, associated with low school grades. Our findings also show that behavioural problems in children are associated with lower school grades independent of parenting style. These findings suggest that parenting styles and child behavioural problems and their interplay may be potential pathways that underpin the influence of parental SES on children's school achievement.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; socioeconomic status; parenting; child behavioural problems; school grades; inequality; Germany